Health and growth - Spence, Michael 1943-; Lewis, Maureen A. 1952- (World Bank, 2009)
This book containes a series of "state of the art" essays on topics related to health and growth. The Commission on Growth and Development (CGD)--in preparing its own Growth Report--wished to take stock of the current state of knowledge and understanding of economic growth, and thus commissioned a series of essays on a range of thematic areas. One such area is health. The following questions are discussed in the book: Does investing in health raise economic growth? Can governments achieve rapid growth or high incomes without investing in health? What are the options and benefits of different analytic approaches to measuring the causal link between health and growth? Have medical advances influenced life expectancy levels? Do health investments lead to higher individual productivity? Why are investments in early childhood development and nutrition important? How do governments invest in improving health status? Where should governments invest in health to improve the welfare and health status of the population? What are the pitfalls in public health care provision and finance? and How can public investments raise health status and household productivity?.